Introduction to Loop Quantum Cosmology - Banerjee, K.; Calcagni, G.; Martín-Benito, M. (Symmetry, Integrability and Geometry: Methods and Applications, 2012)
This is an introduction to loop quantum cosmology (LQC) reviewing mini- and midisuperspace models as well as homogeneous and inhomogeneous effective dynamics.